Why do unionized workers have more nonfatal occupational injuries? - Donado Gomez, Alejandro (ILR review, 2015)
Most empirical studies have estimated a positive union–nonunion “injury gap,” suggesting that unionized workers are more likely than their nonunion counterparts to have a nonfatal occupational injury. Using individual-level panel data for the first time in this type of study, the author explores several explanations for this puzzling result. He finds that controlling for time-invariant individual fixed effects already reduces the gap by around 40%. Some of the explanations he studies contribute to reducing this gap even further. The author does not, however, find evidence of the gap becoming negative, and the impact of unions on nonfatal injuries appears to be insignificant at best.
Article first published online: November 3, 2014
Gesehen am 22.06.2020